Digit ratio (2D:4D), testosterone, cortisol, aggression, personality and hand-grip strength: Evidence for prenatal effects on strength. (September 2016) - Ribeiro, Evaldo; Neave, Nick; Morais, Rosana Nogueiro; Kilduff, Liam; Taylor, Suzan R.; Butovskaya, Marina; Fink, Bernhard; Manning, John T.
Abstract: Background: Digit ratio (2D:4D) is a putative marker for prenatal testosterone and is correlated with performance in many sports. Low 2D:4D has been linked to strength but the evidence is mixed and strength is also influenced by mass, testosterone, and behavioural factors. It has been hypothesised that the 2D:4D-strength correlation may be strongest in challenge conditions when short-term changes occur in steroid hormones. Aims: We tested this suggestion in men. Study design: We used a cross-over study design with a challenge (an aggressive video of rugby tackles) and control (a blank screen) condition. Subjects: 89 healthy men. Outcome measures: Finger lengths (2nd and 4th for both hands), hand-grip strength (HGS), testosterone (T), cortisol (C), aggression (Buss-Perry Aggression Questionnaire) and personality type (Ten Item Personality Measure). In both conditions participants provided saliva samples (for hormone assays). Results: In the challenge condition there was a highly significant increase in HGS, and modest changes in T, physical aggression and emotional stability. HGS correlated negatively with left hand 2D:4D. In a multiple regression, left hand 2D:4D was negatively related to HGS and emotional stability was positively related to HGS. In the control condition HGS was not correlated with 2D:4D. In a multiple regression, BMI, physical aggression, and emotional stability were significantly related to HGS. Conclusions: 2D:4D is a negative correlate of strength in challenge situations. This finding may in part explain associations between 2D:4D and sports performance.